PENGARUH DIFERENSIASI PRODUK, HARGA, ASOSIASI MEREK, KELOMPOK REFERENSI, DAN WORD OF MOUTH (WOM) TERHADAP KEPUTUSAN PEMBELIAN OPPO SMARTPHONE DI KOTA PONTIANAK - admin, Yuyun Maryati B11112026 (Jurnal Manajemen Update, 2016)
The aim of this study is to examine and analyze the effect of variable product differentiation, price, brand association, reference group, and WOM (Word of Mouth) on consumer purchasing decisions of Oppo Smartphone products in Pontianak. It is a survey research. The data were analyzed quantitatively. Data collection method implemented in this study is by questionnaires. The population of this research is the respondents who use Oppo Smartphone products in Pontianak. The sampling technique used is a purposive sampling with a total sample of 105 people. Sample criteria are those which age above or equal to 17 years, live in Pontianak, and Oppo Smartphone Users who acted as purchase decision makers. The analysis technique used is a multiple-linear regression analysis using SPSS 17.0 versippon. This research prove that the product differentiation, price, brand association, and WOM (Word of Mouth) are positive and have significant impact on product purchasing decisions Oppo Smartphone, while the variable reference group had no significant effect on product purchasing decisions Oppo Smartphone. Research model Goodness of Fit result indicated by the coefficient of determination (R2) of 46.5%, which is means that the independent variable in this study is that are product differentiation, price, brand association, reference groups, and word of mouth were able to explain 46.5% of variations in the dependent variable purchase decision. 53.5% of the purchase decisions are influenced by other factors not observed in this study. Keywords: product differentiation, price, brand association, reference groups, WOM (Word of Mouth), the purchase decision.